Is Rheumatoid Arthritis a Risk Factor for Fractures: A Systematic Review of Observational Studies - Gupta, Ambika; Pipe, Stephanie G.; Towheed, Tanveer; Anastassiades, Tassos (Current Rheumatology Reviews, 2020)
Aim: The primary objective was to assess the risk of fractures in adults with RA compared with controls from the general population. The review also assessed an increased risk of fractures in RA patients when accounting for steroid use, RA disease severity or functional impairment. Methods: Citations were screened from MEDLINE, EMBASE, Cochrane Database of Systematic Reviews and CINAHL. Included citations were written in English, including adult patients at least 18 years of age and compared fracture incidence or prevalence between RA patients and a control group. Case-control, cohort and cross-sectional studies were included. Results: There were a total of 3451 citations; after application of the inclusion criteria, 17 studies were selected. In 14 of the 17 studies, there was an increase in the risk of fracture in RA patients compared to controls. In studies that evaluated for glucocorticoid use, four of 13 demonstrated an increased risk of fracture with glucocorticoid use, however, only two of these four studies specifically assessed glucocorticoid use amongst patients with RA. In studies that analyzed RA severity or functional impairment, two of seven demonstrated disease severity or impairment as a risk factor for fracture. There was marked study heterogeneity in terms of patient and fracture characteristics, which was a limitation of the analysis that impeded the ability to make direct comparisons. Conclusion: The risk of fracture in RA patients is elevated when compared to the general population, although the etiology of the increased risk remains to be elucidated.
Keywords: risk of fracture